Characterization and geotechnical properties of coal ash mixtures modified sodium lauryl sulphate - Hong Puan Yee (School of Environmental Engineering, University Malaysia Perlis, 2014)
Most of coal-burning power plant produced residue by-products after burning process such as fly ash and bottom ash with approximate production ratio of 90% fly ash and 20% bottom ash. Previously most of the coal burning wastes especially the fly ash was not managed properly as it were dispersed through the air after it has been entrained in flue gases. Meanwhile the bottom ash as dumped on land area without any treatment. In other aspect, the application of coal ash as mineral filler in polymers hampered by the aggregation of the ash particles and lack of interaction between the ash and polymer.